Social comparison selection in individuals with depression and the role of self-assessment and self-enhancement motives: An experimental investigation - Schlechter, Pascal; Meyer, Thomas; Morina, Nexhmedin (Journal of experimental psychopathology, 2024)
Social comparison plays an important role in depression. However, the process of social comparison selection among depressed individuals remains understudied. This study investigated the choices made by individuals with elevated depression scores (assessed with the Patient Health Questionnaire-8) when exposed to vignettes depicting individuals with varying depression severity and coping ability. We experimentally activated either self-assessment or self-enhancement motives and had participants choose from four vignettes: (1) Mild Depression/Coping Well; (2) Mild Depression/Coping Poorly; (3) Severe Depression/Coping Well; and (4) Severe Depression/Coping Poorly. Our first hypothesis was that most participants would select the Mild Depression/Coping Well vignette, presenting a potential upward social comparison standard (H1). Additionally, we expected higher depression scores to correlate with selecting vignettes featuring greater severity (H2). We further hypothesized that those in the self-enhancement condition would prefer coping poorly vignettes more than those in the self-assessment condition (H3). We conducted a between-subject online experiment (N = 449). Confirming H1, most participants favored the Mild Depression/Coping Well vignette, while the Severe Depression/Coping Poorly vignette was least selected. Supporting H2, higher depression levels were linked to opting for alternative comparison standards over the Mild Depression/Coping Well vignette. Contrary to H3, participants’ choices were not influenced by self-motives.